Brain drain and the disenchantment of being a higher education student in Portugal - Cerdeira, Luísa (2016)
The efforts made by most countries to accelerate economic development have included a significant investment in education. It has been argued that investment in education, particularly higher education, was itself a potential factor in economic development. Education has become a relatively easy means of improving access to the labour market. However, in Portugal, the recent trend has been reversed, and the country now faces a growing number of university graduates in several fields of education and training that do not have a job based on their formal qualifications. Despite the differences of unemployment by area of education and training, unemployment of the young skilled has been a problem in recent years. Therefore, following this unemployment trend, there has been growing the exodus of highly skilled professionals from the Portuguese economy, leaving it with a reduced supply of skilled people. This article discusses the employability of graduates from several academic areas and discusses the educational and economic policies that generate a real brain drain.